Eusebius of Caesarea against Paganism - Kofsky, Aryeh, (Jewish and Christian Perspectives Series;, 2000)
Dealing with the subject of apologetics and polemics against the pagans in Eusebius of Caesarea (c. 260-340), this volume discusses his response to the vigorous political, cultural and religious campaign launched against Christianity in his time. The first part of the book examines the background for Eusebius' apologetic enterprise and his early apologetic writings. The second and main part of the study analyzes major topics in Eusebius' great two-part apologetic work, the Praeparatio Evangelica and the Demonstratio Evangelica , such as the concept of Christian prehistory, prophecy and miracles. The last part deals with Eusebius' tactics and rhetoric and the place of Porphyry - the outstanding pagan polemicist against Christianity - in Eusebius' work. This part closes with a discussion of Eusebius' final apologetic statement in his work The Theophany , reflecting already the recent triumph of Christianity. This publication has also been published in paperback, please click here for details.